Positive electrode

JP7644037B2Active Publication Date: 2025-03-11TOYOTA JIDOSHA KK +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022010733
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-01-27
Publication Date
2025-03-11
Estimated Expiration
2042-01-27

AI Technical Summary

Benefits of technology

【0015】 本開示は、電池の低抵抗化および高耐久化が可能な正極を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644037000003
    Figure 0007644037000003
  • Figure 0007644037000001
    Figure 0007644037000001
  • Figure 0007644037000002
    Figure 0007644037000002
Patent Text Reader

Abstract

To provide a positive electrode that enables low-resistance and high-durability batteries.SOLUTION: In a positive electrode having a positive electrode current collector, an adhesive layer, and a positive electrode layer in this order, the adhesive layer includes spherical carbon and fibrous carbon as a conductive material, and includes an acrylic binder as an adhesive.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway.

[0003] Patent Document 1 discloses the use of a current collecting foil for an electrode, the current collecting foil having an adhesive layer including conductive particles including a base particle, a first conductive layer disposed on the surface of the base particle and formed of silver or copper, and a second conductive layer disposed on the outer surface of the first conductive layer and formed of nickel, and a binder.

[0004] Patent Document 2 discloses an electrode containing a conductive material that combines fine fibrous carbon having a diameter of less than 100 nm and fibrous carbon having a diameter of 100 nm or more.

[0005] Patent Document 3 discloses a positive electrode mixture containing a conductive material that combines carbon fibers and particulate carbon. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-021635 A [Patent Document 2] JP 2010-238575 A [Patent Document 3] JP 2016-058277 A Summary of the Invention [Problem to be solved by the invention]

[0007] There is a demand for batteries with low resistance and high durability. When conventional carbon-coated foil is used as a positive current collector, the contact resistance (foil contact resistance) between the positive layer and the positive current collector (positive current collector foil) decreases due to the excessive addition of conductive material to the positive layer, but the battery durability is low. Increasing the proportion of conductive material in the positive layer can reduce the foil contact resistance, but this blocks some of the multiple ion conduction paths in the positive layer, which in turn increases the internal resistance of the battery. In addition, side reactions between the solid electrolyte and conductive material promote a decrease in battery durability.

[0008] The present disclosure has been made in view of the above circumstances, and has as its main object to provide a positive electrode that can reduce the resistance and increase the durability of a battery. [Means for solving the problem]

[0009] The positive electrode of the present disclosure is a positive electrode having a positive electrode current collector, an adhesive layer, and a positive electrode layer in this order, The positive electrode layer contains spherical carbon and fibrous carbon as conductive materials, The adhesive layer is a conductive material. Carbon-based conductive material and an acrylic binder as an adhesive.

[0010] In the positive electrode of the present disclosure, the positive electrode layer contains a positive electrode active material, The positive electrode active material is LiNi x M 1-x It is a lithium transition metal composite oxide represented by O2. In the lithium transition metal composite oxide, x satisfies 0.5≦x<1, and M may be at least one element selected from the group consisting of Co, Mn, and Al.

[0011] In the positive electrode of the present disclosure, adhesive layer The conductive material includes the spherical carbon and the fibrous carbon. It's okay to do that. In the positive electrode of the present disclosure, When the total volume of the positive electrode layer is taken as 100% by volume, the volume ratio of the conductive material in the positive electrode layer may be 3 to 6% by volume.

[0012] In the positive electrode of the present disclosure, when the total mass of the spherical carbon and the fibrous carbon in the positive electrode layer is taken as 100 mass %, the mass ratio of the spherical carbon may be 7 to 12 mass %.

[0013] In the positive electrode of the present disclosure, the spherical carbon may be acetylene black.

[0014] In the positive electrode of the present disclosure, when the total volume of the adhesive layer is taken as 100% by volume, the volume ratio of the acrylic binder in the adhesive layer may be 50 to 80% by volume. Effect of the Invention

[0015] The present disclosure can provide a positive electrode that can reduce the resistance and increase the durability of a battery. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a cross-sectional schematic diagram showing an example of a positive electrode according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, the embodiments of the present disclosure will be described. In addition, matters other than those specifically mentioned in this specification and necessary for the implementation of the present disclosure (for example, the general configuration and manufacturing process of the positive electrode that do not characterize the present disclosure) can be understood as design matters of a person skilled in the art based on the conventional technology in the field. The present disclosure can be implemented based on the contents disclosed in this specification and the technical common sense in the field. Furthermore, the dimensional relationships (length, width, thickness, etc.) in the drawings do not reflect the actual dimensional relationships. In this specification, the use of "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower limit and upper limit. Furthermore, any combination of upper and lower limits in a numerical range can be used.

[0018] The positive electrode of the present disclosure is a positive electrode having a positive electrode current collector, an adhesive layer, and a positive electrode layer in this order, The positive electrode layer contains spherical carbon and fibrous carbon as conductive materials, The adhesive layer is a conductive material. Carbon-based conductive material and an acrylic binder as an adhesive.

[0019] By using an adhesive layer containing an acrylic binder and a carbon-based conductive material to bond the positive electrode layer and positive electrode current collector, the contact resistance (foil contact resistance) of the positive electrode layer with the positive electrode current collector (positive electrode current collector foil) can be significantly reduced. This eliminates the need to add an excessive amount of conductive material to the positive electrode layer, making it possible to reduce the amount of conductive material in the positive electrode layer, and achieving lower battery resistance and improved durability.

[0020] FIG. 1 is a schematic cross-sectional view showing an example of a positive electrode according to the present disclosure. As shown in FIG. 1, a positive electrode 100 of the present disclosure has a positive electrode current collector 11 and a positive electrode layer 12 , and the positive electrode current collector 11 and the positive electrode layer 12 are bonded together by an adhesive layer 13 .

[0021] [Positive electrode] The positive electrode of the present disclosure has a positive electrode current collector, an adhesive layer, and a positive electrode layer in this order. The positive electrode current collector and the positive electrode layer may be bonded to each other by an adhesive layer.

[0022] [Adhesive layer] The adhesive layer contains spherical carbon and fibrous carbon as conductive materials, and contains an acrylic binder as an adhesive. A composite of spherical carbon and fibrous carbon may also be used as the conductive material. The spherical carbon may be carbon black, etc. The carbon black may be acetylene black, ketjen black, etc. The spherical carbon may be acetylene black. When the spherical carbon contains acetylene black, the electronic conductivity in the positive electrode can be further improved. Examples of the fibrous carbon material include fibrous carbon such as vapor grown carbon fiber, carbon nanotubes, and carbon nanofibers. When the total volume of the adhesive layer is taken as 100% by volume, the volume ratio of the conductive material in the adhesive layer may be 20 to 50% by volume.

[0023] The adhesive is not particularly limited as long as it is an acrylic binder. Examples of the acrylic binder include polyacrylonitrile, polyacrylic acid, polymethyl ester of acrylic acid, polyethyl ester of acrylic acid, polyhexyl ester of acrylic acid, polymethacrylic acid, polymethyl ester of methacrylic acid, polyethyl ester of methacrylic acid, polyhexyl ester of methacrylic acid, and acrylonitrile butadiene rubber (ABR). The acrylic binder has a large change in elastic modulus with respect to temperature, so that it is easy to bond the positive electrode current collector and the positive electrode layer. When the total volume of the adhesive layer is taken as 100% by volume, the volume ratio of the acrylic binder in the adhesive layer may be 50 to 80% by volume. The thickness of the adhesive layer is not particularly limited, but may be 0.5 to 5 μm.

[0024] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain, as optional components, a conductive material, a solid electrolyte, a binder, and the like.

[0025] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for a battery can be used. Examples of the positive electrode active material include lithium alloys, LiCoO2, and LiNi x M 1-x O2 (wherein x satisfies 0.5≦x<1, and M is at least one element selected from the group consisting of Co, Mn, and Al), LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with different elements is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 It is O4 grade. Lithium titanate is, for example, Li4Ti5O 12 etc. Examples of lithium metal phosphates include LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. Examples of transition metal oxides include V2O5, MoO3, etc. Examples of lithium storage intermetallic compounds include Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb, etc. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The positive electrode active material is LiNi x M 1-x The lithium transition metal composite oxide may be represented by the formula: Lithium nickel cobalt aluminate (LiNi 1-x-y Co x Al y O2, x=0.05~0.2, y=0.05~0.2, NCA), Lithium Nickel Cobalt Manganese Oxide (LiNi x Co y Mn 1-x-y O2, x=0.5 to 0.8, y=0.1 to 0.2, NCM), and examples of NCM include NCM-523, NCM-622, and NCM-811. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coating layer may cover, for example, 70% or more, or 90% or more of the surface of the positive electrode active material.

[0026] From the viewpoint of improving the electronic conductivity of the positive electrode layer, the conductive material may be the spherical carbon and fibrous carbon exemplified as the conductive material contained in the adhesive layer, or a mixture or composite thereof. Other known conductive materials may be used, and metal particles may be used. Examples of the metal particles include particles of Ni, Cu, Fe, and SUS. When the total volume of the positive electrode layer is taken as 100 volume%, the volume ratio of the conductive material in the positive electrode layer may be 3 volume% or more and 6 volume% or less, may be 3.51 volume% or more, 5.59 volume% or less, or 4.72 volume% or less. When the total mass of the spherical carbon and fibrous carbon in the positive electrode layer is 100 mass%, the mass ratio of the spherical carbon may be 7 mass% or more and 12 mass% or less, or 8.3 mass% or more, and 11.4 mass% or less. When the total mass of the positive electrode active material in the positive electrode layer is taken as 100 mass %, the mass ratio of the spherical carbon to the positive electrode active material may be 0.3 mass %. When the total mass of the positive electrode active material in the positive electrode layer is taken as 100 mass %, the mass ratio of the fibrous carbon to the positive electrode active material may be 2.34 mass % or more and 4 mass % or less, or may be 3.30 mass % or less.

[0027] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.

[0028] Examples of the binding agent (binder) include polyacrylonitrile, polyacrylic acid, polymethyl ester of acrylic acid, polyethyl ester of acrylic acid, polyhexyl ester of acrylic acid, polymethacrylic acid, polymethyl ester of methacrylic acid, polyethyl ester of methacrylic acid, polyhexyl ester of methacrylic acid, acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), and styrene butadiene rubber (SBR). The binder may be, among others, styrene butadiene rubber (SBR), polyacrylonitrile, polyacrylic acid, polymethyl ester of acrylic acid, polyethyl ester of acrylic acid, polyhexyl ester of acrylic acid, polymethacrylic acid, polymethyl ester of methacrylic acid, polyethyl ester of methacrylic acid, polyhexyl ester of methacrylic acid, and acrylonitrile butadiene rubber (ABR). The content of the binder in the positive electrode layer is not particularly limited.

[0029] The thickness of the positive electrode layer is not particularly limited, but may be, for example, 10 to 100 μm.

[0030] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a paste for forming a positive electrode layer, and the paste for forming a positive electrode layer is applied onto one side of a support and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the paste for forming a positive electrode layer onto one surface of the support is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.

[0031] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a surface pressure of 1 MPa to 2000 MPa and a linear pressure of 1 ton / cm to 100 ton / cm are usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.

[0032] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for a battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0033] [battery] The positive electrode of the present disclosure can be used as the positive electrode of various batteries. The battery of the present disclosure may include a positive electrode, an electrolyte layer, and a negative electrode.

[0034] [Negative electrode] The negative electrode includes a negative electrode layer and a negative electrode current collector.

[0035] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, soft carbon, lithium alone, lithium alloy, Si alone, Si alloy, and Li4Ti5O 12 As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape, a plate shape, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass. The method for forming the negative electrode layer includes a method of applying a paste for forming the negative electrode layer containing a negative electrode active material onto a support and drying the paste, etc. The support may be the same as those exemplified for the positive electrode layer.

[0036] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, and examples of such materials include SUS, copper, and nickel. Examples of the shape of the negative electrode current collector include foil and plate. The planar shape of the negative electrode current collector is not particularly limited, and examples of such shapes include a circle, an ellipse, a rectangle, and any polygon. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, within a range of 1 μm to 50 μm, or within a range of 5 μm to 20 μm.

[0037] [Electrolyte layer] The electrolyte layer includes at least an electrolyte. The electrolyte may be an aqueous electrolyte solution, a non-aqueous electrolyte solution, a gel electrolyte, a solid electrolyte, etc. These may be used alone or in combination of two or more.

[0038] The solvent of the aqueous electrolyte solution contains water as a main component. That is, based on the total amount of the solvent (liquid component) constituting the electrolyte solution (100 mol%), water may account for 50 mol% or more, particularly 70 mol% or more, and further 90 mol% or more. On the other hand, there is no particular upper limit to the proportion of water in the solvent.

[0039] The solvent contains water as a main component, but may contain a solvent other than water. Examples of the solvent other than water include one or more selected from ethers, carbonates, nitriles, alcohols, ketones, amines, amides, sulfur compounds, and hydrocarbons. The solvent other than water may be 50 mol% or less, particularly 30 mol% or less, and further 10 mol% or less, based on the total amount of the solvent (liquid component) constituting the electrolytic solution (100 mol%).

[0040] The aqueous electrolyte used in the present disclosure includes an electrolyte. The electrolyte for the aqueous electrolyte may be a conventionally known one. Examples of the electrolyte include lithium salts, nitrates, acetates, and sulfates of imide acid compounds. Specific examples of the electrolyte include lithium bis(fluorosulfonyl)imide (LiFSI; CAS No. 171611-11-3), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI; CAS No. 90076-65-6), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI; CAS No. 132843-44-8), lithium bis(nonafluorobutanesulfonyl)imide (CAS No. 119229-99-1), lithium nonafluoro-N-[(trifluoromethane)sulfonyl]butanesulfonylamide (CAS No. 176719-70-3), lithium N,N-hexafluoro-1,3-disulfonylimide (CAS No. 189217-62-7), CH3COOLi, LiPF6, LiBF4, Li2SO4, and LiNO3.

[0041] The concentration of the electrolyte in the aqueous electrolyte solution can be appropriately set according to the desired battery characteristics, within a range not exceeding the saturation concentration of the electrolyte in the solvent, because if a solid electrolyte remains in the aqueous electrolyte solution, the solid may inhibit the battery reaction. For example, when LiTFSI is used as the electrolyte, the aqueous electrolyte may contain 1 mol or more of LiTFSI per kg of water, particularly 5 mol or more, and further 7.5 mol or more. The upper limit is not particularly limited, and may be, for example, 25 mol or less.

[0042] The non-aqueous electrolyte solution used generally contains a lithium salt and a non-aqueous solvent. Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2(Li-TFSI), LiN(SO2C2F5)2, and LiC(SO2CF3)3. Examples of the non-aqueous solvent include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, sulfolane, acetonitrile (AcN), dimethoxymethane, 1,2-dimethoxyethane (DME), 1,3-dimethoxypropane, diethyl ether, tetraethylene glycol dimethyl ether (TEGDME), tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide (DMSO), and mixtures thereof. From the viewpoint of ensuring a high dielectric constant and a low viscosity, the solvent may be a mixture of a cyclic carbonate compound having a high dielectric constant and a high viscosity, such as EC, PC, or BC, and a chain carbonate compound having a low dielectric constant and a low viscosity, such as DMC, DEC, or EMC, or a mixture of EC and DEC. The concentration of the lithium salt in the non-aqueous electrolyte may be, for example, 0.3 to 5M.

[0043] A gel electrolyte is generally a gel formed by adding a polymer to a non-aqueous electrolyte solution. Specifically, the gel electrolyte can be obtained by adding a polymer such as polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyvinylidene fluoride (PVdF), polyurethane, polyacrylate, or cellulose to the nonaqueous electrolyte solution described above and gelling the solution.

[0044] The electrolyte layer may be impregnated with an electrolyte such as the above-mentioned aqueous electrolyte solution, and a separator may be used to prevent contact between the positive electrode layer and the negative electrode layer. The material of the separator is not particularly limited as long as it is a porous film, and examples thereof include resins such as polyethylene (PE), polypropylene (PP), polyester, cellulose, and polyamide, among which polyethylene and polypropylene are also suitable. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be a nonwoven fabric such as a resin nonwoven fabric or a glass fiber nonwoven fabric.

[0045] [Solid electrolyte layer] The electrolyte layer may be a solid electrolyte layer made of a solid. The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used in an all-solid-state battery can be appropriately used, and examples of such solid electrolytes include inorganic solid electrolytes such as sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and nitride-based solid electrolytes. The sulfide-based solid electrolyte may contain sulfur (S) as a main component of the anion element. The oxide-based solid electrolyte may contain oxygen (O) as a main component of the anion element. The hydride-based solid electrolyte may contain hydrogen (H) as a main component of the anion element. The halide-based solid electrolyte may contain halogen (X) as a main component of the anion element. The nitride-based solid electrolyte may contain nitrogen (N) as a main component of the anion element.

[0046] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.

[0047] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.

[0048] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.

[0049] Examples of oxide-based solid electrolytes include solid electrolytes containing Li, Y (Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Specific examples of oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O 12 (0≦x≦2), Li5La3Nb2O 12 perovskite-type solid electrolytes such as (Li,La)TiO3, (Li,La)NbO3, (Li,Sr)(Ta,Zr)O3; Nasicon-type solid electrolytes such as Li(Al,Ti)(PO4)3 and Li(Al,Ga)(PO4)3; Li-PO-based solid electrolytes such as Li3PO4 and LIPON (a compound in which some of the O in Li3PO4 is replaced with N); and Li-BO-based solid electrolytes such as Li3BO3 and a compound in which some of the O in Li3BO3 is replaced with C. In the present disclosure, the notation "(A,B,C)" in a chemical formula means "at least one selected from the group consisting of A, B, and C."

[0050] The hydride-based solid electrolyte has, for example, Li and a complex anion containing hydrogen. The complex anion is, for example, (BH4) - , (NH2) - , (AlH4) - , and (AlH6) 3- etc.

[0051] The halide-based solid electrolyte is, for example, represented by the following composition formula (1). Li α M β X γ ...Equation (1) In the composition formula (1), α, β, and γ are each independently a value greater than 0. M includes at least one element selected from the group consisting of metal elements and metalloid elements other than Li. X includes at least one element selected from the group consisting of F, Cl, Br, and I. In the present disclosure, the "metalloid elements" are B, Si, Ge, As, Sb, and Te. The "metal elements" are all elements in Groups 1 to 12 of the periodic table except for hydrogen, and all elements in Groups 13 to 16 of the periodic table except for B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se. In other words, the "metalloid elements" or "metal elements" are a group of elements that can become cations when forming an inorganic compound with a halogen element. More specifically, examples of halide-based solid electrolytes include Li3YX6, Li2MgX4, Li2FeX4, LiAlX4, LiGaX4, LiInX4, Li3AlX6, Li3GaX6, and Li3InX6, where X is at least one selected from the group consisting of F, Cl, Br, and I.

[0052] An example of the nitride-based solid electrolyte is Li3N.

[0053] The solid electrolyte may be in the form of particles from the viewpoint of ease of handling. The average particle size of the solid electrolyte particles is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more, while the average particle size of the solid electrolyte particles is, for example, 25 μm or less, and may be 10 μm or less.

[0054] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.

[0055] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, may be in the range of 60% by mass or more and 100% by mass or less, may be in the range of 70% by mass or more and 100% by mass or less, or may be 100% by mass.

[0056] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.

[0057] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method for forming the solid electrolyte layer includes a method of applying a paste for forming a solid electrolyte layer containing a solid electrolyte onto a support and drying it, and a method of pressurizing a powder of a solid electrolyte material containing a solid electrolyte. The support may be the same as those exemplified for the positive electrode layer. When pressurizing the powder of the solid electrolyte material, a press pressure of about 1 MPa or more and 2000 MPa or less is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.

[0058] The battery may optionally include an exterior body that houses a laminate having a positive electrode collector, a positive electrode layer, an electrolyte layer, a negative electrode layer, and a negative electrode collector in this order, and a restraining member. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin. The restraining member may be any known member usable as a battery restraining member as long as it can apply a restraining pressure in the stacking direction to the laminate. For example, a restraining member having plate-shaped parts that sandwich both surfaces of the laminate, a rod-shaped part that connects the two plate-shaped parts, and an adjustment part that is connected to the rod-shaped part and adjusts the restraining pressure by a screw structure or the like can be used. The adjustment part can apply a desired restraining pressure to the laminate. The restraining pressure is not particularly limited, but may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. By increasing the restraining pressure, there is an advantage that it is easier to improve the contact between the layers. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. If the restraining pressure is too high, the restraining member is required to have high rigidity, and the restraining member may become large.

[0059] The battery may have only one of the above laminates, or may be formed by stacking a plurality of the laminates. The battery may be a primary battery or a secondary battery, but it may be a secondary battery in particular. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as a battery for vehicles. The battery may be an aqueous battery, a non-aqueous battery, an all-solid-state battery, or the like. The battery may be a lithium battery, a lithium ion battery, or the like. Furthermore, the all-solid-state battery may be an all-solid-state lithium secondary battery, an all-solid-state lithium ion secondary battery, or the like. Examples of the shape of the battery include coin type, laminate type, cylindrical type, and square type. The use of the battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the battery may be used as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. The battery of the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.

[0060] In the case where the battery of the present disclosure is an all-solid-state battery, the manufacturing method of the all-solid-state battery may, for example, first form a solid electrolyte layer by applying a paste for forming a solid electrolyte layer to a support and drying it. Then, obtain a positive electrode layer by applying a paste for forming a positive electrode layer containing a positive electrode active material on one side of the solid electrolyte layer and drying it. Thereafter, peel the support from the solid electrolyte layer, apply a paste for forming an anode layer on the other side of the solid electrolyte layer and dry it to form an anode layer, and if necessary, attach a positive electrode current collector to the side of the positive electrode layer opposite the solid electrolyte layer, and attach a negative electrode current collector to the side of the negative electrode layer opposite the solid electrolyte layer to form an all-solid-state battery. EXAMPLES

[0061] [Preparation of adhesive layer coated aluminum foil] VGCF and AB as conductive materials and an acrylic binder (ARONTAC S1551, manufactured by Toa Gosei Co., Ltd.) as an adhesive were weighed so that the volume ratio of the conductive material to the adhesive was conductive material:adhesive=25:75 vol%. NMP was then added to prepare an adhesive layer composition. Next, the adhesive layer composition was applied to one side of an aluminum foil (positive electrode current collector), and the adhesive layer composition was dried at 100°C for 1 hour to obtain an adhesive layer-coated aluminum foil.

[0062] [Preparation of conventional carbon-coated aluminum foil] VGCF and AB as conductive materials and PVdF as adhesive were weighed so that the volume ratio of conductive material to adhesive was conductive material:adhesive=25:75vol%. Then, NMP was added to prepare a carbon coating composition. Next, the carbon coating composition was applied to one side of an aluminum foil (positive electrode current collector), and the carbon coating composition was dried at 100°C for 1 hour to obtain a carbon-coated aluminum foil.

[0063] Example 1 [Preparation of paste for forming positive electrode layer] LiNi as the positive electrode active material 0.8 Co 0.2 Al 0.2 O2 (hereafter referred to as NCA) was used. A rolling fluidized coating device (Powrex Corporation) was used to coat the positive electrode active material particles (LiNi 0.8 Co 0.2 Al 0.2 The composite active material particles having a lithium niobate coating layer were obtained by coating the particles (particles having O2 as the main phase) with lithium niobate and sintering them in an air atmosphere. The composite active material particles, VGCF and AB as conductive materials, solid electrolyte, SBR as a binder, and a solvent were weighed and mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Corporation) to prepare a paste for forming a positive electrode layer. When the total volume of the obtained positive electrode layer was taken as 100% by volume, the volume ratio of the conductive material in the positive electrode layer was adjusted to 3.51% by volume. When the positive electrode active material was taken as 100 mass %, the mass ratio of the spherical carbon AB was adjusted to be 0.3 mass %. When the positive electrode active material was taken as 100 mass %, the mass ratio of the fibrous carbon VGCF was adjusted to be 2.34 mass %. When the total mass of the spherical carbon AB and the fibrous carbon VGCF in the positive electrode layer was taken as 100 mass %, the mass ratio of the spherical carbon AB was adjusted to 11.4 mass %.

[0064] [Preparation of paste for forming negative electrode layer] Li4Ti5O as negative electrode active material 12 The particles, the carbon material as a conductive material, the binder, and the butyl butyrate were mixed in predetermined amounts and mixed for 30 minutes using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) After that, the solid electrolyte was added to the slurry obtained by mixing, and the mixture was mixed again for 30 minutes using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a paste for forming the negative electrode layer.

[0065] [Preparation of paste for forming solid electrolyte layer] Heptane, a heptane solution containing 5% by mass of a butadiene rubber binder, and LiI-LiBr-Li2S-P2S5-based glass ceramic with an average particle size of 2.5 μm as a sulfide-based solid electrolyte were added to a polypropylene container, and mixed for 30 seconds using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken with a shaker for 3 minutes to obtain a paste for forming a solid electrolyte layer.

[0066] [Preparation of negative electrode] Similarly, the paste for forming the negative electrode layer was applied to the negative electrode current collector by the blade method using an applicator. After application, the paste was dried for 30 minutes on a hot plate at 100° C. to obtain a negative electrode having a negative electrode layer on the negative electrode current collector. In all of the Examples and Comparative Examples, the negative electrode layer weight was adjusted so that the negative electrode capacity / specific charge capacity was 1-fold when the positive electrode capacity / specific charge capacity was 200 mAh / g.

[0067] [Preparation of solid electrolyte layer] The paste for forming a solid electrolyte layer was applied onto an aluminum foil by a blade method, and dried for 30 minutes on a hot plate at 100° C. Then, roll pressing was performed at 1 ton / cm to obtain a negative electrode side laminate having a solid electrolyte layer on the negative electrode layer.

[0068] [Preparation of positive electrode] The paste for forming the positive electrode layer was applied onto an aluminum foil by a blade method using an applicator. After application, the paste was dried for 30 minutes on a hot plate at 100° C. to obtain an aluminum foil-positive electrode layer laminate having a positive electrode layer on the aluminum foil. On the solid electrolyte layer of the negative electrode side laminate, an aluminum foil-cathode layer laminate was laminated so that the cathode layer was in contact with the solid electrolyte layer, and pressed at 130°C and 5 ton / cm. Then, the aluminum foil of the aluminum foil-cathode layer laminate was peeled off, and the adhesive layer-coated aluminum foil prepared in the above [Preparation of adhesive layer-coated aluminum foil] was grounded on the exposed cathode layer so that the adhesive layer was in contact with the cathode layer, to obtain a cathode having an adhesive layer-coated aluminum foil and a cathode layer. This resulted in a power generation element having a positive electrode, a solid electrolyte layer, and a negative electrode in this order. The power generation element was enclosed in a laminate and restrained at 80°C and 5 MPa for 20 hours, to attach the adhesive layer-coated aluminum foil to the cathode layer.

[0069] [Preparation of all-solid-state lithium-ion secondary batteries] Thereafter, the power generating element was cooled to 25° C. and the confining pressure was adjusted to 0.5 MPa to form an all-solid-state lithium ion secondary battery cell for evaluation.

[0070] (Examples 2 to 6) A positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1, except that in the above [Preparation of Positive Electrode Layer Forming Paste], the amount of conductive material was set to the value shown in Table 1.

[0071] (Comparative Examples 1 to 6) In the above [Preparation of Positive Electrode Layer Forming Paste], the amount of conductive material was set to the value shown in Table 1. In [Preparation of Positive Electrode], the aluminum foil of the aluminum foil-positive electrode layer laminate was peeled off, and the conventional carbon-coated aluminum foil prepared in the above [Preparation of Conventional Carbon-Coated Aluminum Foil] was grounded on the exposed positive electrode layer in place of the adhesive layer-coated aluminum foil so that the carbon coat was in contact with the positive electrode layer, to obtain a positive electrode having a conventional carbon-coated aluminum foil and a positive electrode layer. This resulted in a power generation element having a positive electrode, a solid electrolyte layer, and a negative electrode in this order. The power generation element was encapsulated in a laminate and restrained at 80°C and 5 MPa for 20 hours, so that the conventional carbon-coated aluminum foil was attached to the positive electrode layer. Aside from these, a positive electrode and an all-solid-state lithium ion secondary battery were obtained in the same manner as in Example 1.

[0072] [Electron conductivity measurement of the positive electrode layer] Using the positive electrodes of Examples 1 to 6 and Comparative Examples 1 to 6, the electronic conductivity of the positive electrode layer was evaluated under the following conditions. Two positive electrodes were prepared from the power generating element before being enclosed in the laminate prepared in the above [Preparation of Positive Electrode], and the two positive electrodes were stacked facing each other and roll pressed at 5 ton / cm. The obtained opposing positive electrodes were punched out, their thicknesses were measured, and then they were enclosed in a laminate and restrained at 5 MPa to prepare a symmetric cell for evaluating electronic conductivity. A constant voltage of -0.10 to +0.10 V was applied to the obtained symmetric cell, the flowing current value was read, the resistance was calculated according to Ohm's law, and the electronic conductivity of the positive electrode layer was calculated from the obtained resistance and the above thickness. The results are shown in Table 1.

[0073] [Table 1]

[0074] [Foil contact resistance measurement] Using the positive electrodes of Examples 1 to 6, the foil contact resistance of the positive electrode layer with the positive electrode current collector foil was evaluated under the following conditions. A positive electrode taken out from the power generating element before being enclosed in the laminate prepared in the above [Preparation of Positive Electrode] was prepared, and the positive electrode was roll pressed at 5 ton / cm. The pressed positive electrode was enclosed in a laminate and restrained at 80°C and 5 MPa for 20 hours to attach an adhesive layer coated aluminum foil to the positive electrode layer. It was then cooled to 25°C and adjusted to a restraining pressure of 0.5 MPa to prepare a foil contact resistance evaluation cell. A constant voltage of -0.10 to +0.10 V was applied to the obtained foil contact resistance evaluation cell, and the current value flowing was read, and the resistance was calculated according to Ohm's law. The resistance value derived from the electronic conduction in the positive electrode layer was subtracted from the obtained resistance value to calculate the foil contact resistance between the positive electrode layer and the positive electrode current collector foil. The results are shown in Table 2. In Comparative Examples 1 to 6, the foil contact resistance of the positive electrode layer with the positive electrode current collector foil was calculated using the positive electrodes of Comparative Examples 1 to 6 under the same conditions as above, except that the conventional carbon-coated aluminum foil prepared in the above [Preparation of conventional carbon-coated aluminum foil] was attached to the positive electrode layer instead of the adhesive layer-coated aluminum foil. The foil contact resistance of each Example and Comparative Example was calculated as a ratio (%) to the pre-durability DC resistance of Example 1, when the pre-durability DC resistance of Example 1 measured in "Measurement of pre-durability DC resistance (DC-IR) of evaluation cell" described later was taken as 100%. The results are shown in Table 2.

[0075] [Charge and discharge of evaluation cell] Using the all-solid-state lithium ion secondary batteries of the evaluation cells of Examples 1 to 6 and Comparative Examples 1 to 6, charging and discharging of the evaluation cells was carried out under the following conditions. Charging: The battery was charged at a constant current equivalent to 0.3C. After the cell voltage reached 2.7V, the battery was charged at a constant voltage. The charging was terminated when the charging current reached an equivalent of 0.01C. Discharge: The cells were discharged at a constant current equivalent to 0.3 C. After the cell voltage reached 1.5 V, the cells were discharged at a constant voltage. When the discharge current reached 0.01 C, the cells were discharged.

[0076] [Measurement of DC resistance (DC-IR) of evaluation cells before endurance] Using the all-solid-state lithium ion secondary batteries of Examples 1 to 6 and Comparative Examples 1 to 6 for evaluation, the direct current resistance before endurance (DC-IR) was measured under the following conditions. The battery was charged at a constant current equivalent to 60C, and the difference between the voltage before charging and the voltage after 10 seconds of charging was divided by the current equivalent to 60C to calculate the voltage. The pre-durability DC resistance of each Example and Comparative Example was calculated as a ratio (%) to the pre-durability DC resistance of Example 1, assuming that the pre-durability DC resistance of Example 1 was 100%. The results are shown in Table 2.

[0077] [Measurement of total resistance of evaluation cell before endurance] For the all-solid-state lithium ion secondary batteries of the evaluation cells of Examples 1 to 6 and Comparative Examples 1 to 6, the foil contact resistance and the DC resistance before durability were added together to calculate the total resistance of the evaluation cells before durability. The results are shown in Table 2.

[0078] [Measurement of DC resistance (DC-IR) after durability test of evaluation cell] Using the all-solid-state lithium ion secondary batteries of Examples 1 to 6 and Comparative Examples 1 to 6 as evaluation cells, the post-endurance direct current resistance (DC-IR) was measured under the following conditions. A specified number of charge / discharge cycles were performed under the same conditions as those described above in [Charge / discharge of evaluation cell], and then the cell was charged at a constant current equivalent to 60C. The difference between the voltage before charge and the voltage after 10 seconds of charging was divided by the current equivalent to 60C to calculate the DC resistance after durability testing. The post-durability DC resistance of each Example and Comparative Example was calculated as a ratio (%) to the pre-durability DC resistance of Example 1, assuming that the pre-durability DC resistance of Example 1 was 100%. The results are shown in Table 2.

[0079] [Measurement of total resistance of evaluation cell after endurance] For the all-solid-state lithium ion secondary batteries of the evaluation cells of Examples 1 to 6 and Comparative Examples 1 to 6, the foil contact resistance and the DC resistance after durability testing calculated above were added together to calculate the total resistance of the evaluation cells after durability testing. The results are shown in Table 2.

[0080] [Measurement of increase rate of DC resistance (DC-IR) after durability test of evaluation cell] For the all-solid-state lithium ion secondary batteries of the evaluation cells of Examples 1 to 6 and Comparative Examples 1 to 6, the post-durability DC resistance of each Example and Comparative Example was divided by the pre-durability DC resistance of each Example and Comparative Example to calculate the increase rate of the DC resistance of the evaluation cells after the durability test. The results are shown in Table 2.

[0081] [Table 2]

[0082] [Evaluation Results] As shown in Tables 1 to 2, in Examples 1 to 6, it was demonstrated that the use of adhesive layer-coated aluminum foils enabled a significant reduction in foil contact resistance between the positive electrode layer and the positive electrode current collector foil compared to the conventional carbon-coated aluminum foils in Comparative Examples 1 to 6. Furthermore, as shown in Table 2, it can be seen that the total resistance before and after durability in Examples 1 to 6 can be reduced compared to Comparative Examples 1 to 6 by the amount of reduction in the foil contact resistance between the positive electrode layer and the positive electrode current collector foil. Furthermore, as shown in Tables 1-2, it can be seen that in Example 6 and Comparative Example 6, the increase rate of direct current resistance (DCIR) after endurance testing is larger than in Examples 1-5 and Comparative Examples 1-5. From this, it can be seen that if the amount of conductive material in the positive electrode layer is increased, the electronic conductivity of the positive electrode layer can be improved, but if the amount of conductive material in the positive electrode layer is too large, the durability of the battery is reduced as a tradeoff. Therefore, by setting the amount of conductive material in the positive electrode layer within a predetermined range, the increase in direct current resistance after endurance testing of the battery can be reduced, and the durability of the battery can be improved. From the above, according to the present disclosure, by using an adhesive layer-coated aluminum foil, the foil contact resistance between the positive electrode layer and the positive electrode current collector foil can be reduced, and the amount of conductive material in the positive electrode layer can be reduced accordingly, thereby realizing low resistance and high durability of the battery. [Explanation of symbols]

[0083] 11 Positive electrode current collector 12 Positive electrode layer 13 Adhesive layer 100 positive electrode

Claims

1. A positive electrode having a positive electrode current collector, an adhesive layer, and a positive electrode layer in this order, The positive electrode layer contains spherical carbon and fibrous carbon as conductive materials, the adhesive layer contains a carbon-based conductive material as a conductive material and an acrylic binder as an adhesive; A positive electrode, wherein a volume ratio of the conductive material in the positive electrode layer is 3 to 6 volume % when the total volume of the positive electrode layer is 100 volume %.

2. A positive electrode as described in claim 1, wherein when the total volume of the adhesive layer is 100 volume %, the volume ratio of the acrylic binder in the adhesive layer is 50 to 80 volume %.

3. The positive electrode layer includes a positive electrode active material, The positive electrode active material is a lithium transition metal composite oxide represented by LiNi x M 1-x O 2 , 3. The positive electrode according to claim 1, wherein in the lithium transition metal composite oxide, x satisfies 0.5≦x<1, and M is at least one element selected from the group consisting of Co, Mn, and Al.

4. A positive electrode described in any one of claims 1 to 3, wherein when the total mass of the spherical carbon and the fibrous carbon in the positive electrode layer is 100 mass%, the mass ratio of the spherical carbon is 7 to 12 mass%.

5. The positive electrode according to any one of claims 1 to 4, wherein the adhesive layer contains the spherical carbon and the fibrous carbon as the conductive material.

6. The positive electrode according to any one of claims 1 to 5, wherein the spherical carbon is acetylene black.

Citation Information

Patent Citations

  • Electrode pole sheet and electrochemical device

    CN110661001A

  • Electrode for lithium ion battery and its manufacturing method

    JP2010238575A

  • Positive electrode mixture, positive electrode, solid battery and manufacturing methods thereof

    JP2016058277A

  • Power storage device

    JP2017069163A

  • Conductive particle, conductive material and connection structure

    JP2019021635A